2019
DOI: 10.3164/jcbn.19-48
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary activation of vitamin D<sub>3</sub> and preventive effect against interstitial pneumonia

Abstract: Calcitriol [1,25(OH)2D3] is usually investigated in studies on the preventive effect of activated vitamin D against interstitial pneumonia. Although cholecalciferol (vitamin D3) can be easily obtained in the diet and has a longer half-life than calcitriol, there have been few investigations of its effect on interstitial pneumonia. We used human pulmonary fibroblast cell lines (HPFCs) and a mouse model of bleomycin-induced pulmonary fibrosis to evaluate whether vitamin D3 was activated in the lungs and had a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 20 publications
1
57
0
6
Order By: Relevance
“…Vitamin D has immuno‐modulatory properties, that include downregulation of pro‐inflammatory cytokines, 3‐7 and has been shown to attenuate lipopolysaccharide‐induced acute lung injury in mice by blocking effects on the angiopoietin (Ang)‐2‐Tie‐2 signalling pathway and on the renin‐angiotensin pathway 8 . Tsujino I et al have recently shown, both in a mouse model of bleomycin‐induced interstitial pneumonia and in human cell lines, that vitamin D3 is locally activated in lung tissue and has a preventive effect on experimental interstitial pneumonitis 9 . Although it is more likely that any protective effect of vitamin D against Covid19 is related to suppression of cytokine response and reduced severity/risk for ARDS, there is also evidence from a meta‐analysis that regular oral vitamin D2/D3 intake (in doses up to 2000 IU/d without additional bolus), is safe and protective against acute respiratory tract infection, especially in subjects with vitamin D deficiency 10 …”
Section: Countries Latitude Degrees Total Cases (N) Total Deaths N (mentioning
confidence: 99%
“…Vitamin D has immuno‐modulatory properties, that include downregulation of pro‐inflammatory cytokines, 3‐7 and has been shown to attenuate lipopolysaccharide‐induced acute lung injury in mice by blocking effects on the angiopoietin (Ang)‐2‐Tie‐2 signalling pathway and on the renin‐angiotensin pathway 8 . Tsujino I et al have recently shown, both in a mouse model of bleomycin‐induced interstitial pneumonia and in human cell lines, that vitamin D3 is locally activated in lung tissue and has a preventive effect on experimental interstitial pneumonitis 9 . Although it is more likely that any protective effect of vitamin D against Covid19 is related to suppression of cytokine response and reduced severity/risk for ARDS, there is also evidence from a meta‐analysis that regular oral vitamin D2/D3 intake (in doses up to 2000 IU/d without additional bolus), is safe and protective against acute respiratory tract infection, especially in subjects with vitamin D deficiency 10 …”
Section: Countries Latitude Degrees Total Cases (N) Total Deaths N (mentioning
confidence: 99%
“…Recently, it has been demonstrated that high levels of vitamin D (directly activated by respiratory tract cells through CYP27B1) could reduce pulmonary fibrosis by decreasing the levels of pro-inflammatory cytokines (IL-1 beta) produced by pulmonary fibroblast cell lines in a mouse model of bleomycin-induced lung fibrosis [47]. In another study vitamin D administration prevented bleomycin-induced lung fibrosis in mice, by decreasing the levels of hydroxyproline and col1a1, col3a1, and alfa-SMA mRNAs [48].…”
Section: Vitamin D and Pulmonary Fibrosismentioning
confidence: 99%
“…The latter effects could be crucial for their assumptive beneficial effects during SARS-CoV-2 infection, since it seems that SARS-CoV-2 initially uses immune evasion mechanisms, which in some patients is followed by immune hyperreaction and cytokine storm (1), as a common pathogenic mechanism of acute respiratory disease syndrome (ARDS) and systemic inflammatory response syndrome (SIRS) development, regardless of the etiological factor. In that sense, the protective effect of vitamin D has been reported in many conditions associated with pneumonia, cytokine hyperproduction, and ARDS (2,8,10), and vitamin D was recently proposed as a repurposed drug for influenza A H5N1 virus-induced lung injury (3). Additionally, some studies suggest the effectiveness of vitamin D as an adjuvant therapy along with antiretroviral agents in HIV-infected patients (5).…”
mentioning
confidence: 99%